Borderlands: Rescaling economic development in Northern England in the context of greater Scottish autonomy. (June 2014) - Shaw, Keith; Robinson, Fred; Blackie, Jonathan
This article argues that the space created by the clearing away of the English regional 'institutional architecture' after 2010 allows local authorities, in particular, to consider new flexible place-based approaches to economic development not possible under the old system. In this context, economic development activities, initiatives and alliances can now be developed to cover geographical areas that 'make sense', rather than being imposed or being chosen through habit: it is an opportunity to rescale or recalibrate traditional spatial approaches to place-based economic development. Here we discuss some implications of that, particularly how local authorities in the North East of England and Cumbria are responding – or could respond – to the potential granting of greater economic and fiscal powers to Scotland resulting from pressures for further devolution and the 2014 referendum on independence. We look at the emerging opportunities for collaborative approaches to cross-border economic development; this is an issue that is virtually absent from any contemporary studies of local economic development in the UK. Drawing upon recent research, the article outlines the case for a 'Borderlands' approach – which brings together the five local authority areas adjacent to the border – to develop joint approaches to economic development in areas such as transport, tourism, business development and superfast broadband. In addition to such cross-border alliances, we also point to opportunities to reinvigorate co-operation between the North East and Cumbria. The prospect of further autonomy for Scotland is stimulating a new interest in the North East, Cumbria and Scotland in working more collaboratively together, but the outcome of that (whatever the referendum result) may depend upon how the Anglo-Scottish border is perceived. We argue that it needs to be seen less as a barrier and more as an enabling mechanism which brings new opportunities for a relationship based on 'co-optition'.